X-ray absorption spectroscopy with time-tagged photon counting: Application to study the structure of Co(I) intermediate of H(2) evolving photo-catalyst - Smolentsev, Grigory (Faraday Discuss, 2014)
In order to probe the structure of reaction intermediates of photochemical reactions a new setup for laser-initiated time-resolved X-ray absorption (XAS) measurements has been developed. With this approach the arrival time of each photon in respect to the laser pulse is measured and therefore full kinetic information is obtained. All X-rays that reach the detector are used to measure this kinetic information and therefore the detection efficiency of this method is high. The newly developed setup is optimized for time-resolved experiments in the microsecond range for samples with relatively low metal concentration (~1mM). This setup has been applied to study a multicomponent photocatalytic system with a Co(dmgBF(2))(2) catalyst (dmg(2−) = dimethylglyoximato dianion), [Ru(bpy)(3)](2+) chromophore (bpy=2,2′-bipyridine) and methyl viologen as the electron relay. On the basis of analysis of hundreds of Co K-edge XAS spectra corresponding to different delay times after the laser excitation of the chromophore, the presence of a Co(I) intermediate is confirmed. The calculated X-ray transient signal for a model of Co(I) state with a 0.14 Å displacement of Co out of the dmg ligand plane and with the closest solvent molecule at a distance of 2.06 Å gives reasonable agreement with the experimental data.